Communicating Hinduism in a Changing Media Context - Jacobs, Stephen (Religion Compass, 2012)
New media forms have a range of implications for the way in which the Hindu community is conceived and Hinduism is practiced. Oral modes of communication continue to have a significant role in the communication of Hinduism, however, Hindus have also made effective, and often innovative, use of all media forms. The use of print made by Hindu reformers, such as Rammohun Roy, was an important feature in the conceptualization of Hinduism as a ‘world religion’. Print technology also made possible the proliferation of visual images, which have now become incorporated into the devotional practices of many Hindus. Hindus have also developed unique genres in film and television, drawing on the rich narrative traditions of Hindu mythology. Hinduism can also be found in cyberspace. Online darśan, online pūjā services and other uses of the Internet have enabled Hindus, both in India and in diaspora, to maintain a connection with gurus, sacred places and other aspects of tradition. These developments in communication technologies are important in understanding Hinduism today, and the way in which it has evolved in a global context.
Keywords: Communication; Hindu; media